Increasing Students' Reading Interest Through the Sami Sabu Program at SD Negeri 1 Samudra Kulon - Eni Suprati; Wakhudin Wakhudin (UM Purwokerto Press, 2025)
The low interest in reading of students at the elementary school level is a serious challenge in efforts to improve the quality of education in Indonesia. This study aims to analyze the effectiveness of the Sami Sabu (One Week One Book) program in increasing students' interest in reading at SD Negeri 1 Samudra Kulon. Using a descriptive qualitative method with a case study approach, data was obtained through observation, interviews and documentation of 147 students and teachers involved in the program. The results showed a significant increase in reading interest indicators, such as the frequency of visits to the library, the number of books read, and student participation in literacy discussions. Supporting factors for the success of the program include active teacher involvement, freedom to choose books, a varied reading collection, and consistent student appreciation. Despite facing challenges such as limited book collections and parental involvement, the Sami Sabu program has proven effective in forming a participatory and enjoyable literacy culture. This program is recommended as an innovative model in supporting the School Literacy Movement at the elementary level.